Vulnerabilities of water and sanitation at households and community levels in face of climate variability and change: trends from historical climate time series in a West African medium-sized town. (2016) - Cissé, Guéladio; Traoré, Doulo; Touray, Sunkaru; Bâ, Hampaté; Keïta, Moussa; Sy, Ibrahima; Koné, Brama; Utzinger, Jürg; Tanner, Marcel
In Kaédi, a secondary city of Mauritania with approximately 71, 000 inhabitants, the analyses of historical climate time series data (1919-2010) and some projections showed a likely occurrence of more frequent heavy rains and higher risks of flooding events in the future. Vulnerability assessments, facilitated through transversal household surveys toward the end of the rainy season that covered the entire city and followed a stratified sampling approach, showed that the community's water supply comprises more than 100 wells, 33% of households report using water from wells for drinking purposes, 12% of households have their own wells in the yard, and 69% of households have latrines in the yard. The analysis also revealed considerable spatial heterogeneity of vulnerability. Considering the risks of cross-contamination of wells water by onsite sanitation facilities during flood events, communities and local governance actors should find appropriate adaptation to climate change strategies for water and health sectors starting with thematic vulnerability maps.